KOMUNIKASI MATEN WELA PADA RITUAL KEMATIAN MASYARAKAT KEDANG NUSA TENGGARA TIMUR - Khasanah, Nurul; Subiyanto, Agus; Nurhayati, Nurhayati (Universitas Sebelas Maret, 2022)
This study is a qualitative descriptive study that discusses maten wela communication pattern in the death ceremony of the Kedang community in Lembata district, East Nusa Tenggara province. The focuses of the discussion are maten wela communication pattern and language stucture of maten wela. The data was analyzed using the comparative linking technique